2022
DOI: 10.1007/s00227-022-04145-5
|View full text |Cite
|
Sign up to set email alerts
|

The cosmopolitan appendicularian Oikopleura dioica reveals hidden genetic diversity around the globe

Abstract: Appendicularian tunicates are some of the most abundant mesozooplankton organisms with key roles in marine trophic webs and global carbon flux. Like most appendicularians with cosmopolitan distributions, Oikopleura dioica Fol, 1872 is considered a single species worldwide based on morphological features that distinguish them from other appendicularians. Despite their abundance, however, there are still only ~ 70 described appendicularian species, compared to over 2800 ascidian tunicates. Here we perform a mole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…Multi-chromosome line plots comparing O. dioica from different locations further revealed that the genome scrambling phenomenon was not restricted to the comparison of Osaka and Okinawa, but instead common amongst all compared genomes (Figure 1B). In general, the extent of genome scrambling increased with increasing genetic distance, as measured by previous analyses of marker genes (Masunaga et al 2022). Comparisons of O. dioica originating from the same geographic region, such as the comparison of two individuals from the subtropical North Pacific population in Okinawa and Kume, showed little scrambling, with large, intact collinear segments of DNA visible.…”
Section: The Scrambled Genomes Of Oikopleura Dioicamentioning
confidence: 64%
See 3 more Smart Citations
“…Multi-chromosome line plots comparing O. dioica from different locations further revealed that the genome scrambling phenomenon was not restricted to the comparison of Osaka and Okinawa, but instead common amongst all compared genomes (Figure 1B). In general, the extent of genome scrambling increased with increasing genetic distance, as measured by previous analyses of marker genes (Masunaga et al 2022). Comparisons of O. dioica originating from the same geographic region, such as the comparison of two individuals from the subtropical North Pacific population in Okinawa and Kume, showed little scrambling, with large, intact collinear segments of DNA visible.…”
Section: The Scrambled Genomes Of Oikopleura Dioicamentioning
confidence: 64%
“…Considering the remarkable similarity of morphology and ecology of the O. dioica cryptic species studied here (Masunaga et al 2022), the extent of scrambling that we have observed in the chromosomal assemblies appears to be unprecedented. In order to relate the rate of scrambling to evolutionary distance, we estimated a species tree and divergence times for O. dioica using orthologues common to chordates (Figure 6, Supplementary Table 2).…”
Section: Evolutionary Framework Of the Unprecedented Genome Scramblin...mentioning
confidence: 80%
See 2 more Smart Citations
“…These differences suggest that the poly-T/A stretches loci may not be conserved in the mitochondrial genomes of different populations or species. Of note, it was recently suggested that O. dioica from Japan and Norway represent different species (Masunaga, et al 2022). The birth and death dynamics of these poly-T/A stretches will be better clarified when genomic and transcriptomic data from a larger appendicularian taxonomic sampling becomes available.…”
Section: Discussionmentioning
confidence: 99%